New Records of Some Euglenoid Algae From Bangladesh (Bangladesh Journal of Plant Taxonomy, 2021)
The following taxa belong to eight species under five genera of euglenoid algae, namely, Euglena anabaena Mainx., Phacus glaber Pochmann (Defl.) Posch, Phacus indicus Skvortzov, Protaspis obovata Skuja, Strombomonas lanceolata (Playfair) Deflandre, Trachelomonas hexangulata (Swir) Playf., T. obovata var. klebsiana Defl. and T. pseudocaudata Defl. are described here for the first time for Bangladesh.Bangladesh J. Plant Taxon. 28(2): 311-315, 2021 (December)